Planning without planner: Enhancing learning through self-assessment / Nurul Afzan Najid ... [et al.] - Najid, Nurul Afzan; Abdul Rahim, Ainatul Fathiyah; Mohd Noor, Rafizah; Yaacob, Nur Ain; Zulkifli, Nursyahida (Universiti Teknologi MARA, Perlis, 2019)
A university environment's freedom and flexibility can derail students who have not mastered timemanagement skills. During high school, they had a rigidly structured schedule but unfortunately, students often struggle to balance their academic, personal and work commitments when they are in the university. In university, the students will be challenged with many competing demands on their time. Consequently, many students simply choose to give up and let the situation takes its course. Without intervention from a lecturer or parents, the student is unlikely to succeed and will end up with low academic results. Even though there are many apps that have been developed to assist them in managing time, the students need to ‘see time’ or in other words make time visual. Therefore, the SCAP is a worthwhile guideline that is specially invented in promoting their time effectively and efficiently.